2002
DOI: 10.1074/jbc.m203368200
|View full text |Cite
|
Sign up to set email alerts
|

Sp1 and Sp3 Transcription Factors Mediate Malondialdehyde-induced Collagen α1(I) Gene Expression in Cultured Hepatic Stellate Cells

Abstract: Malondialdehyde, the end product of lipid peroxidation, has been shown to stimulate collagen ␣1(I) (Col1a1) gene expression. However, mechanisms of this effect are unclear. The purpose of this study was to clarify these mechanisms. Rat hepatic stellate cells were cultured in the presence of 200 M malondialdehyde, and the effects on collagen gene expression and the binding of nuclear proteins to the col1a1 promoter were analyzed. Malondialdehyde treatment induced an increase in the cellular levels of col1a1 mRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 52 publications
2
22
0
1
Order By: Relevance
“…Among them, Sp1 levels were significantly increased when compared with controls in these cells. Findings from previous studies have also demonstrated the Sp1/Sp3 association with the collagen biosynthetic pathway (Chen et al, 1998;Ruiz et al, 2000;Czuwara-Ladykowska et al, 2001;Garcia-Ruiz et al, 2002). Our RT-PCR data also demonstrate ET-induced expression of Sp1, whereas rottlerin and PD98059 attenuated the Fig.…”
Section: Role Of Pkc␦ In Et-induced Collagen Expression 695supporting
confidence: 72%
See 1 more Smart Citation
“…Among them, Sp1 levels were significantly increased when compared with controls in these cells. Findings from previous studies have also demonstrated the Sp1/Sp3 association with the collagen biosynthetic pathway (Chen et al, 1998;Ruiz et al, 2000;Czuwara-Ladykowska et al, 2001;Garcia-Ruiz et al, 2002). Our RT-PCR data also demonstrate ET-induced expression of Sp1, whereas rottlerin and PD98059 attenuated the Fig.…”
Section: Role Of Pkc␦ In Et-induced Collagen Expression 695supporting
confidence: 72%
“…One study on osteoblastic cells suggests the involvement of PKC and ERK pathways in TGF-␤ 1 -induced type I collagen expression (Palcy and Goltzman, 1999). Several previous reports have implicated the role of Sp1 and Sp3 in collagen transcription in various models (Li et al, 1995;Chen et al, 1998;Ihn and Tamaki, 2000;Ruiz et al, 2000;Czuwara-Ladykowska et al, 2001;Garcia-Ruiz et al, 2002). In the present study, we show a role for PKC, ERK1/2, and Sp1 in ET-induced type I collagen expression in cardiac myoFb.…”
supporting
confidence: 64%
“…The best-studied component of hepatic scar is collagen type I, the expression of which is regulated both transcriptionally and posttranscriptionally in hepatic stellate cells by a growing number of stimuli and pathways. A detailed review of collagen gene regulation in stellate cells is beyond the focus of this review, but several recent references are recommended (7,188,257,258,260,354,528,(617)(618)(619)652).…”
Section: Perpetuationmentioning
confidence: 99%
“…Similar to the aforementioned net activation of a signaling cascade following inhibition of a signaling protein, the inhibition and alkylation of the lipid and protein dual phosphatase PTEN (phosphatase and tensin homolog) was demonstrated to coincide with, and postulated to mediate, stimulation of PI3K/Akt signaling by exposure of cells to HNE [ 76 ]. Further examples of such alkylations by lipid peroxidation products inducing pathophysiologically relevant signaling processes include the stimulated expression of the proinfl ammatory protein cyclooxygenase-2 (COX-2) via stress-responsive kinase p38 MAPK upon exposure to HNE [ 77 ], or the stimulation of collagen expression (a crucial step in the pathogenesis of fi brosis) in fi broblasts [ 78 ] or hepatic stellate cells [ 79 ] following exposure to MDA.…”
Section: Lipid Peroxidation Productsmentioning
confidence: 99%